Studi Kepustakaan Peran Bimbingan Konseling dalam Mencegah Kasus Bullying di Sekolah - Siti Nurajijah; Sofiyah, Zulaehatus (Journal of Islamic Education Counseling, 2022)
This study was conducted to determine the role of counseling guidance in preventing cases of bullying in schools. In this modern era, bullying cases are becoming more and more common. The perpetrators of this bullying usually start with verbal words through social media or other means. Especially among teenagers. It’s no wonder that nowadays there are so many bullies in schools. In addition, many victims of bullying experience adverse effects on their physical and psychological aspects. To prevent this bullying behavior. This study aims to provide ideas for preventing bullying by using counseling guidance services and using individual counseling to prevent cases of bullying in schools. In this case, the researcher uses the library research method. The data collection method used by the researcher is the documentation method. The data collection technique used is content analysis. The results of this study are, what factors are the causes of bullying cases, and how bullying cases occur with the help of counselors through individual counseling and counseling services